Consensus guideline for the diagnosis and management of mannose phosphate isomerase‐congenital disorder of glycosylation. Issue 4 (21st April 2020) - Čechová, Anna; Altassan, Ruqaiah; Borgel, Delphine; Bruneel, Arnaud; Correia, Joana; Girard, Muriel; Harroche, Annie; Kiec‐Wilk, Beata; Mohnike, Klaus; Pascreau, Tiffany; Pawliński, Łukasz; Radenkovic, Silvia; et al.
Abstract: Mannose phosphate isomerase‐congenital disorder of glycosylation (MPI‐CDG) deficiency is a rare subtype of congenital disorders of protein N ‐glycosylation. It is characterised by deficiency of MPI caused by pathogenic variants in MPI gene. The manifestation of MPI‐CDG is different from other CDGs as the patients suffer dominantly from gastrointestinal and hepatic involvement whereas they usually do not present intellectual disability or neurological impairment. It is also one of the few treatable subtypes of CDGs with proven effect of oral mannose. This article covers a complex review of the literature and recommendations for the management of MPI‐CDG with an emphasis on the clinical aspect of the disease. A team of international experts elaborated summaries and recommendations for diagnostics, differential diagnosis, management, and treatment of each system/organ involvement based on evidence‐based data and experts' opinions. Those guidelines also reveal more questions about MPI‐CDG which need to be further studied.